Role of honey in male and female reproductive health and fertility - Hamad Alfarisi, Hamad Abdulsalam; Hamad Zubi, Zainab Bubakr (The Academy of Sciences Malaysia, 2024)
Complementary and alternative medicine is widely used and rapidly growing in developing and developed nations. Honey is an important and unique natural product that has been used since ancient times as a therapeutic agent. Recently, attention has been increased toward its use for the prevention and treatment of numerous diseases as well as for improving and maintaining overall well-being. Traditionally, the consumption of honey is a common practice in some cultures as they believe that honey can enhance fertility and vitality. The efficacy of honey in promoting male and female reproductive health and treating fertility-related problems has been evaluated in experimental studies and clinical trials. The prime goal of this review is to highlight the importance of honey in male and female reproductive health by summarising the data collected from both experimental studies and clinical trials on the role of honey in male and female reproductive health.